Performance of Budgeting, Accountability System for Government Institutions, Performance Internal Control and Accountability Performance Report of Government Agencies in East Kalimantan. - Latif, Imam Nazarudin (Archives of Business Research, 2018)
The form of the accountability report for regional financial management for one budget year for central government agencies for one fiscal year is in the form of Government Institutional Performance Accountability Reports (LAKIP), in which this financial report contains annual performance reports and accountability for the performance of a regional government or central government agency. To ensure that the budget that has been set is carried out properly and in accordance with the goals of the organization, it is necessary to apply controls. the purpose of this research is to explain the causal relationship between research variables by testing the hypotheses that have been formulated. In this study will explain the causal relationship between internal or exogenous variables in the form of Performance Budgeting, Government Agency Performance Accountability System (SAKIP), and Government Institution Performance Accountability (AKIP) in the form of external variables or endogenous Internal Control 1 and external or endogenous variables 2 Performance Accountability Report Government Agencies (LAKIP). From the results of the study showed that the effect of Performance Budgeting had no significant effect on internal control, while the results of other variables have a significant effect on the Government Institutional Performance Accountability System (SAKIP), and Government Institutional Performance Accountability (AKIP), Internal Control and Government Institution Performance Accountability Reports (LAKIP)